Improved electrical performance and transparency of bottom-gate, bottom-contact single-walled carbon nanotube transistors using graphene source/drain electrodes - Shin, Hyeonwoo; Oh, Jinwoo; Kim, Youngjin; Son, Jeong Gon; Lee, Changhee; Shin, Keun-Young (한국공업화학회, 2020)
A highly transparent and high-performance random-network single-walled carbon nanotubes (r-SWCNTs) transistor was successfully fabricated by using chemical vapor deposition-grown graphene source/drain (S/D) electrodes. The bottom-gate, bottom-contact geometry was selected for the graphene S/D contact r-SWCNT (Gr-SWCNT) transistor because of its enhanced gate modulation and good sustainability. A palladium S/D contact r-SWCNT (Pd-SWCNT) transistor with the same device geometry was also fabricated for a comparative study. The transmission line method demonstrated that the resistivity of graphene was small enough (similar to 0.95 Omega mu m) to be used as S/D electrodes in a single transistor device, and the contact resistance of Gr-SWCNTs was much lower than that of Pd-SWCNTs. Particularly, the correlation between the applied gate voltage and the sheet resistance is strongly dependent on the r-SWCNT film density. The resulting Gr-SWCNT transistor exhibits high mobility and good on/off current ratio compared to the Pd-SWCNT transistor. The high charge injection originated from the ohmic contact behavior and dense r-SWCNT channel formation by the enhancement of selective wetting due to the surface energy matching between the r-SWCNT semiconductor and graphene S/D electrodes. Thus, this approach can encourage creating highly transparent and high-performance carbon-based field effect transistor. (C) 2019 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.